Simultaneous Rapid Detection of Aflatoxin B1 and Ochratoxin A in Spices Using Lateral Flow Immuno-Chromatographic Assay - Xue Zhao (MDPI AG, 2021)
Spices are susceptible to contamination by aflatoxin B1 (AFB1) and ochratoxin A (OTA), which are both mycotoxins with high toxicity and carcinogenicity. In this study, we aimed to develop an immuno-chromatographic strip test for the simultaneous quantification of AFB1 and OTA in spices by spraying the coupled antigens AFB1–ovalbumin (AFB1–OVA) and OTA–ovalbumin (OTA–OVA) on a nitrocellulose membrane. The test strip had high sensitivity, good specificity, and strong stability. The detection limits of these two mycotoxins in Chinese prickly ash, pepper, chili, cinnamon, and aniseed were 5 μg/kg. The false positivity rate was 2%, and the false negativity rate was 0%. The maximum coefficient of variation was 4.28% between batches and 5.72% within batches. The average recovery rates of AFB1 and OTA in spices were 81.2–113.7% and 82.2–118.6%, respectively, and the relative standard deviation (RSD) was <10%. The actual sample detection was consistent with high performance liquid chromatography analysis results. Therefore, the immuno-chromatographic test strips developed in this study can be used for the on-site simultaneous detection of AFB1 and OTA in spices. This method would allow the relevant regulatory agencies to strengthen supervision in an effort to reduce the possible human health hazards of such contaminated spices.